Beyond the Presidential Threshold: How Cebong and Kampret Political Identities Shape Social Media Discourse - Urai Panzi; Jagad Aditya Dewantara; sulistyarini sulistyarini; Wibowo Heru Prasetiyo; Jacob Shimrumun Loraa (UIN Sunan Gunung Djati, 2023)
The polemic regarding the Presidential Threshold policy has caused conflict in society and hampered Indonesia's political development. This study aims to prove the impact of the Presidential Threshold policy on the political identity of two groups of people who are often referred to as